Effects of activity tracker-based counselling and live-web exercise on breast cancer survivors' sleep and waking time during Italy's COVID-19 lockdown. Issue 1 (2nd January 2022) - Di Blasio, Andrea; Morano, Teresa; Lancia, Federica; Viscioni, Gianluca; Di Iorio, Angelo; Grossi, Simona; Cianchetti, Ettore; Pippi, Roberto; Gobbo, Stefano; Bergamin, Marco; D'eugenio, Anna; Masini, Laura; et al.
ABSTRACT: The aim of the study was to compare the effects of weekly personal feedback, based on objectively measured physical activity, on daily sleep in breast cancer survivors (BCS) with those of an intervention that also included online supervised physical exercise sessions (OSPES). BCS benefiting from both personal feedback and OSPES (n = 24), from pre-lockdown (T0) to the first month (T1) of the national lockdown, experienced an increase in both total (p ≤ 0.001) and restorative (p ≤ 0.001) sleep time, inverting their trend from the first month of lockdown to its end (total sleeping time T1 vs. T2 0.01 ≤  p < .001, T1 vs. T3 p ≤ 0.001; restorative sleeping time T1 vs. T2 0.05 ≤  p < .01, T1 vs. T3 p ≤ 0.001). Supportive technology, together with the reception of weekly tailored advice and OSPES seems to improve both quality and quantity of sleep.